Human Rights and Artificial Intelligence: An Urgently Needed Agenda - Risse, Mathias (Revista Publicum, 2018)
Artificial intelligence generates challenges for human rights. Inviolability of human life is the central idea behind human rights, an underlying implicit assumption being the hierarchical superiority of humankind to other forms of life meriting less protection. These basic assumptions are questioned through the anticipated arrival of entities that are not alive in familiar ways but nonetheless are sentient and intellectually and perhaps eventually morally superior to humans. To be sure, this scenario may never come to pass and in any event lies in a part of the future beyond current grasp. But it is urgent to get this matter on the agenda. Threats posed by technology to other areas of human rights are already with us. My goal here is to survey these challenges in a way that distinguishes short-, medium-term and long-term perspectives.